Analisis Penggunaan Dana Desa dalam Pembangunan Infrastruktur Menurut Undang-Undang Nomor 3 Tahun 2024 di Desa Bagan Serdang Kabupaten Deli Serdang Tahun 2020-2024 (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to analyze the use of Village Funds in infrastructure development in Bagan Serdang Village, Deli Serdang Regency, during the 2020–2024 period, as well as to identify the inhibiting factors based on the provisions of Law Number 3 of 2024 concerning Villages. The research method used is normative-empirical legal research with a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. Data analysis was carried out through the stages of reduction, presentation, and verification to obtain a comprehensive picture. The results of the study show that the use of Village Funds in Bagan Serdang Village during the period was directed toward infrastructure development such as concrete-paved roads, jetty roads, drainage systems, clean water facilities, and retaining walls, which were generally in line with the principles of transparency, accountability, and public interest as stipulated in the Village Law. However, its implementation still faces several obstacles, namely limited budgets that are not always proportional to development needs, technical and geographical factors such as tidal flooding, land issues due to overlapping ownership, diverse social dynamics of the community, and external factors such as the covid-19 pandemic, which diverted a large portion of the budget to social assistance programs. Therefore, more adaptive management strategies, increased capacity of village officials, and active community participation are needed so that Village Funds can be utilized optimally in accordance with the objectives of sustainable village development.